2022
DOI: 10.3389/fcimb.2022.841995
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Bacterial Microbiome Differs Between Healthy Controls and Those With Asthma and Allergic Rhinitis

Abstract: Perturbation of the microbiome has numerous associations with the phenotypes and progression in chronic airways disease. However, the differences in the nasal microbiome in asthma and allergic rhinitis (AR) have not been defined. We examined whether the nasal microbiome would vary among different comorbidities in asthma and AR and that those differences may be associated with the severity of asthma. Nasal lavage fluid was collected from 110 participants, including 20 healthy controls, 30 subjects with AR, 30 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
3
25
1
Order By: Relevance
“…15 However, knowledge on microbial variance in the upper airways of asthmatics is still fragmentary. It was shown that alpha diversity of the nasal microbiome communities is reduced in patients with asthma and comorbid allergic rhinitis (AR), 16 which is in contrast to the asthma-associated increase in alpha diversity observed in this study. However, 62% of the asthmatic patients analysed in our study exhibited asthma without AR.…”
contrasting
confidence: 95%
“…15 However, knowledge on microbial variance in the upper airways of asthmatics is still fragmentary. It was shown that alpha diversity of the nasal microbiome communities is reduced in patients with asthma and comorbid allergic rhinitis (AR), 16 which is in contrast to the asthma-associated increase in alpha diversity observed in this study. However, 62% of the asthmatic patients analysed in our study exhibited asthma without AR.…”
contrasting
confidence: 95%
“…The nasal bacteriomes of the studied samples were composed of four dominant phyla and 10 dominant genera ( Figure 1 and Table 1 ). All these taxa have been previously described in the nasal cavity of asthmatic, rhinitic or healthy individuals [ 35 , 37 , 38 , 47 , 48 , 49 , 51 , 52 , 69 , 103 , 104 ], where they are considered normal residents. The characterized bacteriotas were mainly comprised of commensal taxa [ 103 , 104 ], but some genera (e.g., Moraxella , Streptococcus , Haemophilus , Neisseria and Staphylococcus ) including pathogenic species associated to asthma [ 33 , 34 , 35 , 36 , 39 , 40 , 55 , 57 , 58 , 59 , 105 ] and allergic rhinitis [ 47 , 48 , 49 , 50 , 51 , 52 ] were also detected.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies using high-throughput sequencing (HTS), mainly of the 16S rRNA gene, have already demonstrated that the bacterial communities living in the respiratory airways (i.e., airway bacteriome) play a significant role in the onset, development and severity of both asthma [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and allergic rhinitis [ 47 , 48 , 49 , 50 , 51 , 52 ]. Microbial HTS has also shown that the nasal cavity is a major reservoir for opportunistic pathogens (e.g., Moraxella , Streptococcus , Haemophilus , Neisseria , and Staphylococcus ), which can spread to other sections of the respiratory tract and potentially induce asthma, rhinitis and other respiratory illnesses [ 31 , 35 , 36 , 37 , 38 , 39 , 41 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The importance of the nasal microbiota as a gatekeeper to respiratory health is well known, and their intimate links to chronic airways disease are beginning to be elucidated [ 60 ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples are represented by Streptococcus pneumonia , Haemophilus influenzae , and Moraxella catarrhalis , commonly present in the nose of healthy children ( 15 ), further strengthening the idea that a healthy nasal microbiota is not only required to protect from environmental microbes but also to keep commensal opportunistic pathogens under control. Various clinical conditions, including allergic rhinitis, chronic rhinosinusitis, asthma, and respiratory tract infections from both viral and nonviral pathogens, have been associated with changes in the composition of nasal microbiome ( 8 , 16 , 17 ). Although causative relationships are difficult to draw, it is becoming increasingly clear that associations can be unveiled by combining the specific changes of the microbiota with the onset and/or the clinical course of the disease.…”
Section: Entering the Nose: The First Gate To Airborne Diseasesmentioning
confidence: 99%